Facebook use and its relationship with sport anxiety - Encel, K.; Mesagno, C.; Brown, H. (Journal of Sports Sciences, 2017)
Social media (e.g., Facebook and Twitter) use has increased considerably since its inception; however, research examining the relationship between social media use and sport has not progressed as rapidly. The purpose of the current study was to explore the prevalence rates of Facebook use among athletes around and during sport competitions and to investigate the relationships between sport anxiety and Facebook use. Two hundred and ninety-eight athletes of varying levels completed measures for sport anxiety and Facebook use, which included descriptive information about Facebook use prior to, during and following competitions. Results indicated that 31.9% of athletes had used Facebook during a competition and 68.1% had accessed Facebook within 2 h prior to competition. Time spent on Facebook prior to competition was significantly (and positively) correlated with the concentration disruption component of sport anxiety. Furthermore, regression analyses revealed that having push notifications enabled on an athletes` phone predicted 4.4% of the variability in sport anxiety. The percentage of athletes who accessed Facebook within 2 h of, or during, a competition is somewhat alarming considering the importance of psychological preparation in sport, which may compromise optimal psychological readiness and may lead to increased sport anxiety.